Exogenous IL‐6 induces mRNA splice variant MBD2_v2 to promote stemness in TP53 wild‐type, African American PCa cells. Issue 7 (24th May 2018) - Teslow, Emily A.; Bao, Bin; Dyson, Greg; Legendre, Christophe; Mitrea, Cristina; Sakr, Wael; Carpten, John D.; Powell, Isaac; Bollig‐Fischer, Aliccia
Abstract : African American men (AAM) are at higher risk of being diagnosed with prostate cancer (PCa) and are at higher risk of dying from the disease compared to European American men (EAM). We sought to better understand PCa molecular diversity that may be underlying these disparities. We performed RNA‐sequencing analysis on high‐grade PCa to identify genes showing differential tumor versus noncancer adjacent tissue expression patterns unique to AAM or EAM. We observed that interleukin‐6 (IL‐6) was upregulated in the nonmalignant adjacent tissue in AAM, but in EAM IL‐6 expression was higher in PCa tissue. Enrichment analysis identified that genes linked to the function of TP53 were overrepresented and downregulated in PCa tissue from AAM. These RNA‐sequencing results informed our subsequent investigation of a diverse PCa cell line panel. We observed that PCa cell lines that are TP53 wild‐type, which includes cell lines derived from AAM (MDA‐PCa‐2b and RC77T), did not express detectable IL‐6 mRNA. IL‐6 treatment of these cells downregulated wild‐type TP53 protein and induced mRNA and protein expression of the epigenetic reader methyl CpG binding domain protein 2 (MBD2), specifically the alternative mRNA splicing variant MBD2_v2. Further investigation validated that upregulation of this short isoform promotes self‐renewal and expansion of PCa cancer stem‐like cells (CSCs). In conclusion, this report contributes to characterizing gene expression patterns in high‐grade PCa and adjacent noncancer tissues from EAM and AAM. The results we describe here advance what is known about the biology associated with PCa race disparities and the molecular signaling of CSCs. Abstract : RNA‐sequencing analysis of patient specimens and a systematic investigation of the role of exogenous and endogenous IL6 across a diverse prostate cancer cell line panel brings new understanding of IL6 expression patterns and signaling that drive prostate cancer stem cell‐like cells, and underscores the potential importance of IL6 in PCa race disparities.